Analisis Pengaruh Citra Merek dan Promosi Online terhadap Keputusan Pembelian Produk BSI Oleh Generasi Z di BSI Merr Surabaya - Farhan Mahmud Azyumardiazra; Sirajual Arifin (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2026)
This study, titled “analysis of the influence of brand image and online promotion on generation z’s decision to purchase bsi product at bsi merr surabaya”, examines the effect of brand image (X1) and online promotion (X2) on the purchasing decisions (Y) of Generation Z consumers at the BSI Merr Surabaya branch. Using a quantitative research approach, data were collected from 100 respondents aged 20–27 years through purposive sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of WarpPLS 7.0 software. The results indicate that both brand image (X1) and online promotion (X2) have a significant and positive influence on Generation Z’s decision to purchase BSI products. Among the two variables, online promotion (X2) shows a stronger impact, highlighting its importance in engaging digitally savvy consumers. These findings emphasize the need for companies to strengthen digital marketing strategies while maintaining a solid brand image to effectively influence purchasing behavior. The study underscores the strategic relevance of optimizing both factors to enhance consumer engagement and drive purchase decisions among Generation Z.